Early Laboratory Predictors for Necessity of Renal Replacement Therapy in Patients With Spontaneous Deep-Seated Intracerebral Hemorrhage - Schenk, Lorena M.; Schneider, Matthias; Bode, Christian; Güresir, Erdem; Junghanns, Christoph; Müller, Marcus; Putensen, Christian; Vatter, Hartmut; Zimmermann, Julian; Schuss, Patrick; Lehmann, Felix (Frontiers in Neurology, 2021)
Objective: The need for continuous renal replacement therapy (CRRT) in patients with deep-seated intracerebral hemorrhage (ICH) requires sustained intensive care and often postpones further rehabilitation therapy. Therefore, an early identification of patients at risk is essential. Methods: From 2014 to 2019, all patients with deep-seated ICH who were admitted to intensive care for >3 days were included in the further analysis and retrospectively reviewed for the need for CRRT. All patients underwent CRRT with regional citrate anticoagulation for continuous veno-venous hemodialysis (CVVHD). Outcome was evaluated after 3 months using the modified Rankin scale. A multivariate analysis was performed to identify potential predictors for CRRT in patients with deep-seated ICH. Results: After applying the inclusion criteria, a total of 87 patients with deep-seated spontaneous ICH were identified and further analyzed. During the first 48 h after admission, 21 of these patients developed early acute kidney injury (AKI; 24%). During treatment course, CRRT became necessary in nine patients suffering from deep-seated ICH (10%). The multivariate analysis revealed “development of AKI during the first 48 h” [p = 0.025, odds ratio (OR) 6.1, 95% confidence interval (CI) 1.3–29.8] and “admission procalcitonin (PCT) value >0.5 μg/l” (p = 0.02, OR 7.7, 95% CI 1.4–43.3) as independent and significant predictors for CRRT in patients with deep-seated ICH. Conclusions: Elevated serum levels of procalcitonin on admission as well as early development of acute renal injury are independent predictors of the need for renal replacement therapy in patients with deep-seated intracerebral bleeding. Therefore, further research is warranted to identify these vulnerable patients as early as possible to enable adequate treatment.